Improving Learning Outcomes of Class VIII-E Students in Civics Subjects through the Talking Stick Type Cooperative Learning Model at SMP Negeri 13 Mataram - Nensi Yucandry W Samba; Hariyanto Hariyanto; Edy Kurniawansyah; M. Ismail (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The aims of this study were (1) to determine the learning outcomes of class VIII-E students in Civics subjects at SMP Negeri 13 Mataram, (2) to determine the application of the talking stick type cooperative learning model to Civics subjects at SMP Negeri 13 Mataram, (3) to find out the improvement of student learning outcomes in class VIII-E through the talking stick type cooperative learning model in Civics subjects at SMP Negeri 13 Mataram. This research uses classroom action research method. Classroom action research is research by using an action to identify learning problems in the classroom in an effort to improve the learning process. From the results of classroom action research shows that the increase in student learning outcomes. This can be seen from the pre-cycle learning with the percentage of learning completeness is 53.3% and the average value is 67.2%. In the first cycle there was an increase in learning completeness by 90.5% and an average value of 85%.